Satellite image analysis of human caused changes in the tundra vegetation around the city of Vorkuta, north-European Russia - Virtanen, T.; Mikkola, K.; Patova, E.; Nikula, A. (Elsevier, 2005)
http://www.elsevier.com/locate/issn/02697491 In this paper we present what kind of human impacted changes can be found in dwarf birch (Betula nana) dominated shrub tundra vegetation around the large industrial complex of Vorkuta in the north-European Russian tundra. Using fieldwork data and Landsat TM satellite image we could identify two impact zones: (1) Pollution zone (150–200 km2). In this zone most of the lichen species are absent. Changes in vegetation communities' species composition in all main plant groups are obvious. Willows especially are more dominant than in the unpolluted sites. (2) Slight pollution/disturbance zone (600–900 km2). Here vegetation changes are mainly similar but less so than the changes in the first zone. Particularly, the amount of herbs and grasses is increased when compared to unpolluted areas. The pollution zones are spatially connected to the main emission sources in the area. Zones spread furthest to the northeast, matching the prevailing winds during winter.